Repolarisation of the immune-suppressive millieu of the ovarian tumour using targeted therapeutics - Khan, Adnan R. (2012)
Ovarian cancer is a disease which is fatal in the majority of cases. The evolution of surgery and chemotherapy over the past 30 years has resulted in improvements in overall and progression-free survival. However, the rate of relapse in ovarian cancer is very high, suggesting that current treatment strategies are ineffective. Therefore, to overcome the poor prognosis of ovarian cancer, immunotherapeutic strategies have been devised such as the use of anti-CTLA-4 antibody therapy in melanoma. The principle that the immune system can effect either cancer development or clearance has been the subject of debate for over a century. Clinical results of novel immunotherapeutic approaches that aim to exploit and enhance this immunogenicity have had mixed successes such as IL-2 therapy in renal cell carcinoma. It is clear that whilst many tumours possess antigenic component in their make-up, they do not stimulate durable and effective immune responses in vivo. This may reflect the fact that tumours develop a network of escape mechanisms to circumvent tumour-specific immunity.